2022
DOI: 10.1136/bmjopen-2021-055473
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the implementation of guideline-based prophylactic antiemetic therapy for chemotherapy-induced nausea and vomiting in Japan: a protocol for a hospital-based qualitative study

Abstract: IntroductionChemotherapy-induced nausea and vomiting (CINV) decrease patients’ quality of life and negatively impact treatment outcomes. Although standard prophylactic antiemetic therapy for acute CINV recommended by guidelines is effective, poor guideline implementation is a worldwide problem. In Japan, prophylactic antiemetic therapy is relatively well implemented for chemotherapy associated with high emetogenic risk, while implementation gaps are observed for that with low emetogenic risk.Although most repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The aim is to make the prescription of premedication as safe as possible, and it has been shown that prescribing with a software reduces the risk of error. 47,48…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim is to make the prescription of premedication as safe as possible, and it has been shown that prescribing with a software reduces the risk of error. 47,48…”
Section: Discussionmentioning
confidence: 99%
“…The aim is to make the prescription of premedication as safe as possible, and it has been shown that prescribing with a software reduces the risk of error. 47,48 In addition, Nolte et al 49 studied the impact of creating a checklist to standardise the prescription of premedication. This action enabled compliance with the recommendations to rise from 73% to at least 87%, and the premedication budget to be reduced by more than two.…”
Section: Role Of the Different Actorsmentioning
confidence: 99%
“…This process used three rounds of a modified-Delphi technique, followed by cognitive interviews, and deliberations among the research team, SAB, and PAB members to identify, operationalize, and pre-test CFIR survey items. Many studies using the CFIR to implement and evaluate clinical practices rely largely on qualitative methods to identify salient constructs [34][35][36][37][38][39]. Our approach is unique in employing an interactive process that begins with examining all CFIR constructs to prospectively and quantitatively examine implementation barriers and facilitators [15,17].…”
Section: Discussionmentioning
confidence: 99%